Ocular Defects in Photosensitive Epilepsy - Ebere C. Anyanwu; John Ehiri (The Scientific World Journal)
Patients with photosensitive epilepsy are susceptible to seizures due to photoparoxysmal response (PPR). This response adversely precipitates factors that modify the functional status of the visual system. Such factors may or may not be evident superficially, but may lead to ocular defects due to trauma, hormonal imbalance, abnormal intraocular pressure (IOP), or any other reflex-inducing stimuli. The extent to which photosensitive epileptic patients suffer from PPR-related ocular defects has not been documented fully. In this investigation, ocular defects in patients with photosensitive epilepsy are studied using visual-evoked response (VER). A total of 212 photosensitive epileptic patients were studied to ascertain the magnitude and distribution of ocular defects using the changes in EEG and visual-evoked potential (VEP); 51% of the patients were female, the age range was 146 years. The major ocular defects and complications found were visual field defects, optic nerve abnormalities, nystagmus, cataracts, amblyopia, and migraine. These findings were analyzed according to age and sex. The relationship between the ocular abnormalities and the interpretations of the changes in the characteristics of the VEP indicated that optic-related atrophies, visual defects, optic neuritis, chiasmal compression, nystagmus, migraine headache, cataracts, and amblyopia were prevalent in photosensitive epileptic patients at varying degrees. The results showed that although ocular defects in photosensitive epilepsy may not be obvious differentially, VEP can be used in their diagnosis, contrary to earlier studies reporting that VEP is not of much value in epilepsy diagnosis.